2015
DOI: 10.1007/s00300-015-1833-6
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon and biogenic silica in marine sediments in the vicinities of the Antarctic Peninsula: spatial patterns across a climatic gradient

Abstract: To assess whether sea floor sediment reflects the characteristics of the upper water column, organic carbon (OC) and biogenic silica (bSi) were measured in seventeen 5-cm-long sediment cores recovered within a climatic gradient from the northwestern Weddell Sea (WS) to the Drake Passage (DP) across the Bransfield Strait (BS). Climate settings in the study area vary from dry and cold (polar) conditions with seasonal sea ice coverage in the WS to a more humid and warm (oceanic) environment where no seasonal sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Even in the Weddell Sea, chlorophyll and sea-ice dynamics were important. These results indicate that the typical polar environmental conditions of the atmosphere and upper water column had an important effect on the seabed biota, even at depths of down to 600 m. A similar conclusion was drawn in the study based on Agassiz-trawl catches from the same study area ) and confirmed by a biogeochemical flux study (Isla 2016). In two shallow-water studies in East Antarctica ) and the Ross Sea (Cummings et al 2006), referring to spatial scales similar to the intermediate ones of our analyses, sea ice parameters turned out to be important drivers.…”
Section: Intermediate To Large-scale Patterns and Driverssupporting
confidence: 89%
“…Even in the Weddell Sea, chlorophyll and sea-ice dynamics were important. These results indicate that the typical polar environmental conditions of the atmosphere and upper water column had an important effect on the seabed biota, even at depths of down to 600 m. A similar conclusion was drawn in the study based on Agassiz-trawl catches from the same study area ) and confirmed by a biogeochemical flux study (Isla 2016). In two shallow-water studies in East Antarctica ) and the Ross Sea (Cummings et al 2006), referring to spatial scales similar to the intermediate ones of our analyses, sea ice parameters turned out to be important drivers.…”
Section: Intermediate To Large-scale Patterns and Driverssupporting
confidence: 89%
“…It is commonly accepted that the Antarctic benthic realm can be considered as a rather stable system with little variation in environmental parameters such as temperature, salinity, and water currents, whereas the pelagic realm is considered as highly seasonal with distinct summer/winter cycles, especially in primary production and sea ice extension (Gallardo 1987;Clarke 1988;Bathmann et al 1991;Scharek et al 1994;Arntz et al 1994;Arrigo et al 1998;Palanques et al 2002;Smith et al 2006;Isla et al 2009Isla et al , 2011Rossi et al 2013;Flores et al 2014;Isla 2016b). While the stability of the benthos and instability of the pelagos are commonly accepted, the intrinsic biotic and abiotic factors of both are highly dependent on local water mass properties and circulation, as well as wind, sea ice, and topographic conditions (e.g., Barry and Dayton 1988; Barthel and Gutt 1992;Gleitz et al 1994;Dunbar et al 1998;Ducklow et al 2006;Isla et al 2009;Hauck et al 2010;Barnes 2015).…”
Section: Seasonality and Particle Fluxmentioning
confidence: 99%
“…Most of the primary production is proposed to be generated within the seasonal sea ice zone, especially in waters close to the retreating sea ice edge, where water column stability and nutrient concentrations are high. Driven by melting of sea ice, these locations also act as seeding grounds for primary production in the euphotic zone, enabled by released sea ice algae and enhanced input of nutrients (Scharek et al 1994;Sedwick and DiTullio 1997;Sedwick et al 2000;Arrigo et al 2008;Bertolin and Schloss 2009;Isla et al 2009;Isla 2016b). The primary production in the seasonal sea ice zone was estimated to be 1300 Tg C y −1 , of which 420 Tg C y −1 are generated in the marginal sea ice zone and roughly 5% of production of the seasonal sea ice zone is produced by sea ice algae (Lizotte 2001).…”
Section: Pelagic Realmmentioning
confidence: 99%
See 1 more Smart Citation
“…For echinoids, a shift in food preference with changing environmental conditions was studied (Michel et al 2015). Not only organism-based aspects were investigated, but also ecological and sediment processes, including interactions between biota and biogeochemical factors (Isla 2015). The study on the spatial ecology of ascidians, which are assumed to be especially sensitive to environmental change (Segelken-Voigt et al 2016), was based on seabed images, which are publicly available in the data repository PANGAEA (www.pangaea.de).…”
mentioning
confidence: 99%